Addressing the needs of early childhood teachers in promoting motor development through a co-design process. Issue 5 (20th October 2021) - Capio, Catherine M.; Chan, Wai Ling; Li, Echo Si
ABSTRACT: Teachers play a crucial role in promoting motor development in early childhood. A series of focus-group discussions was conducted with kindergarten teachers in Hong Kong to co-design movement activities. This paper reports the process and implications to teachers' professional development.